Factors Affecting the Incidence of Hypertension in Menopause Using Literature Studies - Gregorius Katanna; Wiwik Agustina; Afrihal Afiif (PROFESSIONAL HEALTH JOURNAL, 2022)
ABSTRACT Introduction : Non Communicable Diseases (NCD) has become a health problem community both globally, nationally, regionally and even locally. World Health Organization (WHO) in 2015 reported that NCD killed 40 million people every year or equivalent of 70% of deaths worldwide. One of disease classified as non communicable which is dangerous namely hypertension. Hypertension is an important factor as a trigger for Non Communicable Diseases (NCD) such as heart disease, stoke, and others which is currently the number one cause of death scourge in the world. Menopause is one of the triggers for hypertension. Method : This study aims to analyze the factors that affected the incidence of hypertension in menopause. The study uses 4 databases namely E-resources, EBSCO, DOAJ, and Google Scholar using criteria inclusion and exclusion. Data analysis used descriptive method by summarizing research journals. There are 13 journals used. Results : From 13 articles, it was found several factors that cause hypertension in menopause such as age, physical activity, food / beverage intake, stress, and obesity. Conclusion : At menopause, there is a decrease in estrogen secretion resulting in constriction of blood vessels (vasoconstriction) which can cause blood pressure to rise. Henceforth, it is hoped that the community, especially families and respondents, will be able to know more about their health conditions, especially blood pressure so that they can check more frequently and also be able to maintain their lifestyle